Etika dan Gaya Komunikasi Akademik di Twitter/X Studi Kasus Percakapan Dosen-Mahasiswa - Vista Lara Sati, Nores; Uswatun Hasanah; Syahrul R; Elfia Sukma; Norliza Jamaluddin (Indo-MathEdu Intellectuals Journal, 2025)
The main objective of the study is to understand how communication ethics are applied in academic interactions on social media and to identify patterns of communication styles used by both parties. The method used is a case study with a qualitative analysis of lecturer and student conversations on Twitter/X. The data sources in this study consist of tweets and replies posted by lecturers and students in an academic context. The data collection technique was carried out by collecting relevant conversations using certain keywords and a specified time period. The data collected was then analyzed using content analysis techniques, where researchers identified themes, patterns, and ethical elements that emerged in the interaction. The results of the study indicate that although Twitter/X provides a fast and informal communication space, academic interactions still maintain certain ethical elements such as politeness and professionalism. However, challenges were also found in the form of potential misinterpretations and misunderstandings due to character limits and short writing styles. These findings indicate the importance of ethical awareness in academic communication on social media in order to create effective and harmonious interactions. In conclusion, this study contributes to developing academic communication guidelines that are in accordance with the characteristics of digital platforms, which are very relevant in the current era of educational digitalization